Retraction notice to “Advancing Toward a Sustainable Future in subtropical semi-arid type climatic zone: Iraq case - The Progress of Solar Photovoltaic Energy Implementation” [e-Prime - Advances in Electrical Engineering, Electronics and Energy 8 (2024) 100565] - Qusay Hassan; Sameer Algburi; Marek Jaszczur; Maha Barakat; Aws Zuhair Sameen; Bashar Mahmood Ali; Dunya Jameel Kassid (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/policies/article-withdrawal).This article has been retracted at the request of the Editor-in-Chief.In investigating concerns regarding late-stage authorship changes to this article, the editors reached out to the authors for an explanation. In addition to the concerns regarding the late-stage authorship changes the editors were unable to verify the contribution of any of the added authors and the author responses were unsatisfactory.Maha Barakat, Bashar Mahmood Ali, and Dunya Jameel Kassid were added to this paper after the first round of revision. One author was removed at revision one. These changes were made without explanation and without the exceptional approval by the handling Editor, which is contrary to the journal policy on changes to authorship. The editor therefore feels that the findings of the manuscript cannot be relied upon and that the article needs to be retracted.